Are trees forms? On formalism, material feminism, and historical literature. Issue 3 (1st September 2020) - Phillips, George Micajah
ABSTRACT: This essay draws on formalist cultural studies and material feminism to argue for a new approach in modernist studies, which I call formalist materialism, that reads ecological forms alongside aesthetic forms. Such an approach may have distinct advantages. As a theoretical model working from these traditions, it illuminates a new direction for formalist attention to literature by connecting it to embodiment, ecology, and material substances, and a novel path for feminist materialists by suggesting historical objects and situations where human and nonhuman agencies might be clearer. As I demonstrate in readings of Karel Čapek and Virginia Woolf, this model of reading also might help reinvigorate ways of approaching early-twentieth-century modernism in our time of ecological crisis, but without looking for signs of our concerns and epistemologies in the past.